Remote sensing data for monitoring agricultural production and economic activity: Application in Egypt - Abay, Kibrom A.; Abdelradi, Fadi; Kassim, Yumna; Guo, Zhe (International Food Policy Research Institute, 2022)
This policy note showcases two examples on how remote sensing data can be used for monitoring agricultural production and economic activities. The first case aims to generate granular data on agricultural production, which remain scarce in Egypt and the MENA region. The second case demonstrates the potential of remote sensing data to monitor economic activities during the COVID19 pandemic. Based on these data and together with other recent findings, we provide the following recommendations to facilitate post-COVID-19 recovery in Egypt: ► Targeting of stimulus and recovery packages based on the economic repercussions experienced across geographies and sectors ► Identifying and supporting promising value chains which experienced a significant slowdown in economic activities ► Diversifying economic activities and markets to improve the resilience of agri-food systems. ► Investment in data infrastructure to monitor and respond to future shocks. This may be supported by scale up of digital solutions, which proved to be effective in sustaining business activities even during the pandemic.